2021
DOI: 10.3390/molecules26030615
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of the Acetylenic Derivative of Betulin Phosphate Involves Induction of Necrotic-Like Death in Breast Cancer Cells In Vitro

Abstract: Betulin (BT) is a natural pentacyclic lupane-type triterpene exhibiting anticancer activity. Betulin derivatives bearing propynoyloxy and phosphate groups were prepared in an effort to improve the availability and efficacy of the drug. In this study, a comparative assessment of the in vitro anticancer activity of betulin and its four derivatives was carried out using two human breast cancer cell lines: SK-BR-3 and MCF-7. In both studied cell lines, 30-diethoxyphosphoryl-28-propynoylbetulin (compound 4) turned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Studies on endometrial adenocarcinoma and melanoma cell lines revealed activation of caspase-3 dependent apoptosis after treatment with 28-O-propynoylbetulin [36][37][38]. However, the MCF7 breast cancer cell line turned out to be highly resistant to that compound [39]. As continuation of the compound development, we inserted the diethoxyphosphoryl group at C29 position of the acetylenic derivative of betulin.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on endometrial adenocarcinoma and melanoma cell lines revealed activation of caspase-3 dependent apoptosis after treatment with 28-O-propynoylbetulin [36][37][38]. However, the MCF7 breast cancer cell line turned out to be highly resistant to that compound [39]. As continuation of the compound development, we inserted the diethoxyphosphoryl group at C29 position of the acetylenic derivative of betulin.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of the synthesized compounds were determined based on their 1 H- 13 C-and 31 P-NMR (Bruker AVANCE III HD 600, Billerica, MA, USA, deuterated chloroform), IR (IRAffinity-1 FTIR spectrometer; Shimadzu Corporation, Kyoto, Japan, KBr pellet), and MS spectra (Bruker Impact II, Billerica, MA, USA). MThe melting point, R f parameters, and spectroscopic ( 1 H, 13 C, and 31 P NMR) data for the tested compounds were consistent with the literature information [10,44]. (The most important data characterizing compounds EB5 and ECH147 are presented in Table S2, Supplementary Materials).…”
Section: Eb5 and Ech147 Synthesismentioning
confidence: 99%
“…On the other hand, the main morphological changes in apoptosis are chromatin condensation and blebbing, together with cell shrinkage and nuclear fragmentation. 17–19 Ferroptosis is also morphologically different from necroptosis, which is characterized by swelling of the cells and intracellular organelles, and membrane rupture. 18 20 21 …”
Section: Characteristics Of Ferroptosismentioning
confidence: 99%
“…On the other hand, the main morphological changes in apoptosis are chromatin condensation and blebbing, together with cell shrinkage and nuclear fragmentation. [17][18][19] Ferroptosis is also morphologically Open access Open access different from necroptosis, which is characterized by swelling of the cells and intracellular organelles, and membrane rupture. 18 20 21 It was recently shown in human trophoblast cells (primary PHT cells and the BeWo human trophoblast cell line) that macroblebbing of the membrane occurred during ferroptosis.…”
Section: Morphological Changes During Ferroptosismentioning
confidence: 99%